A Comparative Study on the Flexural Behaviour of Rubberized and Hybrid Rubberized Reinforced Concrete Beams - Hasan Aied Alasmari; B. H. Abu Bakar; A. T. Noaman (Civil Engineering Journal, 2019)
This paper aims to investigate the flexural behaviour of the rubberized and hybrid rubberized reinforced concrete beams. A total of fourteen beams, 150×200 mm in cross-section with 1000 mm in length, were subject to a laboratory test over an effective span of 900 mm. The sand river aggregate was replaced by 10%, 12.5%, and 15% of crumb rubber (volume).   The hybrid structure contained two double layers: 1) rubberized reinforcement concrete at the top layer of the beam and 2) reinforcement concrete at the bottom layer of the concrete beam. The static responses by the flexural test of all the beams were evaluated in terms of their fresh properties, failure patterns, total energy, flexural strength, stiffness, and ultimate deflection, modulus of rupture, strain capacity, and ductility index. The results showed that there were improvements when the hybrid beams were used in most cases such as failure pattern, ultimate load, stiffness, modulus of rupture, and stress. The rubberized concrete beams showed improvements in the strain capacity as illustrated in strain gauges and stress-strain curves, toughness, ultimate deflection, and ductility index. The findings of the study revealed an improved performance with the use of the hybrid beams. This has resulted in the implementation of innovative civil engineering applications in the engineering sustainable structures.